ON THE ISSUE OF STUDYING THE KARAKALPAK EPIC (CAHIERS MAGELLANES-NS, 2024)
In the modern world, the issue of revival, preservation and promotion of national traditions, among which great importance is attached to the musical heritage, is becoming increasingly relevant. In world science, until now, dastans have been analyzed on the basis of the criteria and norms of philology, aesthetics, and literary criticism. On this basis, musical scientific hypotheses are popularized on the study of musical science, namely, the musical culture of Central Asia, the spiritual heritage of oral folk art, dastan art, and the direction of traditional performance at an international level.